Association of Lymph Node Count and Survival after Primary Retroperitoneal Lymphadenectomy for Nonseminomatous Testicular Cancer. Issue 5 (3rd May 2022) - Patel, Hiren V.; Srivastava, Arnav; Kim, Sinae; Patel, Hiten D.; Pierorazio, Phillip M.; Bagrodia, Aditya; Masterson, Timothy A.; Ghodoussipour, Saum B.; Kim, Isaac Y.; Singer, Eric A.; Jang, Thomas L.
Abstract : Purpose: Retroperitoneal lymph node dissection (RPLND) for men with clinical stage (CS) I or II testicular nonseminomatous germ cell tumor (NSGCT) has both staging and therapeutic implications. We aimed to investigate the impact of lymph node count (LNC) on outcome after primary RPLND for men with CS I or II NSGCT using a nationally representative data set. Materials and Methods: A retrospective analysis of men who received a primary RPLND for CS I or II NSGCT was performed using the National Cancer Database. The Kaplan-Meier method was used to determine overall survival (OS) according to LNC. Logistic regression analyses were used to identify factors associated with LNC >20 and factors predictive of lymph node-positive (pN+) disease after primary RPLND. Results: Of 1, 376 men who comprised our analytical cohort, 50.1% and 49.9% had 1–20 lymph nodes (LNs) and >20 LNs removed, respectively. Five-year OS rates were 96.4% and 99.1% for men with 1–20 and >20 LNs resected, respectively (p=0.004). A higher proportion of men with >20 LNs removed were treated at academic centers, had private insurance, presented with higher AJCC (American Joint Committee on Cancer) CS and were more likely to have pN+ disease, compared to those with 1–20 LNs removed. Factors significantly associated with pN+ disease after RPLND include higher AJCC CS and LNC (per 10-count increase). Conclusions: Higher LNC after primary RPLND significantly increases the likelihood of identifying pN+ disease and is associated with improved OS. Our data support the therapeutic implications of a thoroughly performed RPLND in the primary setting.